Analyse the Role of Cadre, Parenting and Food Intake to Nutrition Status of Toddler - Undatun Ni'mah; Nia Sari; Yuly Peristiowati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Nutrition problems are still a serious problem. Nutrition disorders that occur in infants and toddlers affect the growth and development, both in infancy and future, so it needs attention. The role of cadres, parenting parents and food intake given to infants. The purpose of this study was to determine the factors that affect the nutritional status of children under five years in the working area of ​​Puskesmas Kertosari Banyuwangi. This research design use analytic design with cross sectional approach. The population of all under-fives suffering from malnutrition status in the work area of ​​Kertosari Puskesmas is 47 children. The sampling technique used cluster random sampling with a sample of 42 respondents. The research instrument used questionnaires, 24 hour recall obeservation sheet and anthropometry. The results were analyzed using logistic regression test. The result of this research is the influence of the role of cadre to the nutritional status of under-five children with ρ = 0.005 <0.05 and OR = 22.8 which means the chance to help the toddler in overcoming the nutritional status is 22.8 times bigger than the role of the inactive cadre. While in the pattern of care obtained ρ = 0.003 <0.05 denagn = 0.112 means there is influence between parental parenting to the nutritional status of children. Where the parenting patterns are applied authoritarian, then the parenting pattern has a risk of no nutritional problems 0.112 times greater in the parent's patterns permissive or democratic. There is influence between food intake on nutritional status of children under five years in working area of ​​Puskesmas Kertosari of Banyuwangi Regency with ρ = 0,004 <0,05. The most dominant factor affecting the nutritional status of children under five is the factor of food intake given to toddlers, with the effect of 13,924.To be able to increase the intake of food that is by observing the diet and eating consumption in accordance with the nutritional needs of every toddler, in consuming everyday foods familiarize with balanced nutrition menu.